2011
DOI: 10.1002/uog.8903
|View full text |Cite
|
Sign up to set email alerts
|

Sequence of changes in myocardial performance index in relation to aortic isthmus and ductus venosus Doppler in fetuses with early‐onset intrauterine growth restriction

Abstract: Objective To explore the sequence of changes in myocardial performance index (MPI) and aortic isthmus (AoI) and ductus venosus (DV) flow in fetuses with earlyonset intrauterine growth restriction (IUGR). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
9

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 36 publications
1
64
0
9
Order By: Relevance
“…However, it requires training to achieve the necessary competence to perform the exam. In the study conducted by Cruz-Martinez et al [18], the learning curve to achieve competence in the Mod-MPI measurement was evaluated; the maximum disagreement between examiners was 10% and 65 measurements on an average were required to attain significant competence. Meriki et al [26] propose refinement adjustments in the apparatus where the MPI measurements will be performed, because these adjustments can influence the inter-observer repeatability as well as the opening and closing clicks valve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it requires training to achieve the necessary competence to perform the exam. In the study conducted by Cruz-Martinez et al [18], the learning curve to achieve competence in the Mod-MPI measurement was evaluated; the maximum disagreement between examiners was 10% and 65 measurements on an average were required to attain significant competence. Meriki et al [26] propose refinement adjustments in the apparatus where the MPI measurements will be performed, because these adjustments can influence the inter-observer repeatability as well as the opening and closing clicks valve.…”
Section: Discussionmentioning
confidence: 99%
“…This Mod-MPI improved the inter-observer reproducibility associated with the original coefficient [16]. Cruz-Martinez et al [18] indicated that on an average, the MPI values are above the 95 th percentile three weeks before the pulsatility index (PI) change in the ductus venosus of foetuses with early-onset FGR.…”
Section: Introductionmentioning
confidence: 93%
“…In addition, progressive changes in AoI Doppler values are strongly correlated with those occurring in the DV [32]. These reasons are proposed as determinants to explain the poor predictiveness of this vessel for perinatal mortality [8,12,13,14,33,34]. On the contrary, AoI has been suggested to have a clear association with postnatal neurological morbidity [15,35] since it is a marker of brain centralization.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis used in the present study was based on a CHAID model that automatically chooses the independently associated parameters for decision making, while our previous analysis was performed manually for each group. A recent longitudinal study on cardiovascular changes in IUGR showed that the MPI becomes altered at an earlier stage than the DV [33], and this may explain a weaker association with perinatal mortality. These results do not preclude the clinical value of MPI but illustrate that larger studies should be conducted in order to refine the assessment of the potential contribution of the MPI to monitoring of early-onset IUGR.…”
Section: Discussionmentioning
confidence: 99%
“…MPI in IUGR fetuses has been evaluated in a number of different studies by conventional and tissue Doppler [6,11,30,31,32,33,34,83,84,85,86,87,88]. In fetuses followed longitudinally, MPI was identified as one of the earliest Doppler parameters affected and remained elevated throughout the different stages of deterioration with a steeper curve of deterioration compared with other Doppler indices (aortic isthmus and ductus venosus pulsatility indices) [34,87].…”
Section: Clinical Application Of Mpimentioning
confidence: 99%